Soybean (Glycine max L.) Yield and Yield Component Under Different Planting Time and Foliar Application of Humic Acid - Ali, Shara Salih; Mirza, Chnar Hama Noori (Kurdistan Journal of Applied Research, 2024)
A triplicate field experiment laid out in randomized complete block design was conducted to evaluate the effect of foliar application of humic acid rates (HAR) at Bakrajo, Sulaimani which is (located at 35°32’52.8"N and 45°21’16.6"E) belongs to Kurdistan region of Iraq with the silty clay soil type. Five different Humic Acid rates (HAR) which were (0 (control), 2,4,6,8 g/L) and two cultivation period (CP) which were cultivation Period 1 (CP1) on 15 May 2022 and cultivation Period 2 (CP2) on 1st of June 2022. The effect of foliar Humic acid rates application methods was highly significant on the Pod No./ Plant, Empty Pod/Plant, Seed Weight / Plant (g) and yield (kg/ha) and significant on the 1000 Seed Weight (g). While, the effect of cultivation period (CP) was highly significant only for the Pod No./ Plant and the insignificantly affected the other parameters including Empty Pod/Plant, Seed No./ Pod, 1000 Seed Weight (g), Weight / Plant (g) and yield (kg/ha). The maximum Pod No./ Plant, Empty Pod/Plant, Seed Weight / Plant (g) and yield (kg/ha) and significant on the 1000 Seed Weight (g) were observed under foliar application of HAR of 6 g/L and the best cultivation period for sowing humic acid was (CP1) which was on 15 May.